Supratentorial Intraventricular Tumors: Experience from a Tertiary Neurosurgical Center in Nepal - Thakur, Alok Chandra; Dhamala, Ijan; Soti, Nischal; Jha, Prabhat; Bohara, Sandeep; Shrestha, Dipendra Kumar; Pradhanang, Amit Bahadur; Sedain, Gopal (Nepal Journal of Neuroscience, 2026)
Introduction: Supratentorial intraventricular tumors are rare central nervous system neoplasms located deep within the ventricular system. Their proximity to eloquent neural pathways and critical vascular structures makes surgical management technically challenging. Data from low and middle income regions remain limited. This study evaluates the clinical features, histopathological patterns, surgical approaches, and outcomes of patients treated at a tertiary neurosurgical center in Nepal.Material and Method: A retrospective observational study was conducted including 27 consecutive patients who underwent surgical resection of supratentorial intraventricular tumors between September 2020 and August 2025. Demographic, clinical, radiological, histopathological, operative, and postoperative data were collected and analyzed. Statistical analysis included descriptive statistics, chi-square testing, logistic regression modeling, and calculation of confidence intervals. Institutional Review Committee approval was obtained prior to study initiation.Results: The mean age was 24.9 ± 13.2 years, with a male predominance of 21 (77.8%). Headache was the most common presenting symptom, occurring in 14 (51.9%) patients. Colloid cyst was the most frequent histopathological diagnosis, identified in 7 (25.9%) patients, followed by subependymal giant cell astrocytoma in 5 (18.5%) and choroid plexus tumors in 5 (18.5%). The transcortical-transventricular approach was most frequently utilized in 14 (51.8%) cases. Postoperative hydrocephalus requiring cerebrospinal fluid diversion occurred in 5 (18.5%) patients. Overall mortality was observed in 3 (11.1%) patients. No statistically significant association was found between tumor type or surgical approach and postoperative complications.Conclusion: Microsurgical resection remains the cornerstone of management for supratentorial intraventricular tumors in resource-limited settings. Although acceptable surgical outcomes can be achieved, postoperative hydrocephalus continues to be a significant challenge. Larger prospective multicenter studies are needed to optimize surgical strategies and improve patient outcomes.